Clinical application, evaluation and analysis of influencing factors analysis of on tuberculosis ?-Interferon enzyme-linked immunosorbent assay - Ning Xu; Wenlian Tu; Taicheng Jin; Rui Zheng; Xiaoqin Mao; Lei Zhu (Journal of the Pakistan Medical Association, 2021)
Objective: To assess sensitivity and specificity of the interferon gamma release assay test, and to pinpoint the influencing factors that should be taken care of in clinical application. Methods: The study was conducted at the First People's Hospital in the Yunnan Province of China from October 2018 to March 2019, and comprised samples collected from outpatient and inpatients. To detect mycobacterium tuberculosis, acid-fast staining on sputum smear was performed on relevant tissues suspected of extrapulmonary tuberculosis. Tuberculosis interferon gamma release assay test and pathology samples were examined. Tuberculosis-specific cell reaction assay kit was used for sampling. SysmexXN-2000 haematology analyser, VACUETTE SRS100/II and Beckman Coulter AU5800 were used to perform various analyses. Data was grouped and analysed using R statistical software. Results: Of the 960 samples, 516(53.75%) cases tested positive for tuberculosis infection and 444(46.25%) tested negative. The sensitivity of the pathological results was 86% and the specificity was 96%. The sensitivity of the interferon gamma release assay test was 95% and specificity 82%. Interferon release test, pathological results and final diagnosis showed significant comparisons (p<0.05). Significant relationships were also established for factors, such as age, interferon release quantity, lymphocyte, C-reactive protein and counts of mono-nuclear cell (p<0.05). Conclusions: Interferon gamma release assay test was found to have high consistency with pathological results and final diagnosis and can be used as a subsidiary to traditional clinical imaging and pathological judgment. Key Words: Tuberculosis, Interferon release, CRP, Hormone use. Continuous...